(untitled) (Norfolk, U.K., 2008)
Evidence has been piling up that small RNAs are able to control gene expression by directed control of epigenetic modifications at particular genomic loci. Biological scientists from the anglophone world, France, and Japan review research findings into the RNA regulation of gene expression, an acknowledgment and understanding
Keywords: RNA,Genetic regulation,Điều chỉnh di truyền